Prevalence and risk factors associated with birth asphyxia among neonates delivered in Ethiopia: A systematic review and meta-analysis. - Ritbano Ahmed (Public Library of Science (PLoS), 2021)
Background A number of primary studies in Ethiopia address the prevalence of birth asphyxia and the factors associated with it. However, variations were seen among those studies. The main aim of this systematic review and meta-analysis was carried out to estimate the pooled prevalence and explore the factors that contribute to birth asphyxia in Ethiopia. Methods Different search engines were used to search online databases. The databases include PubMed, HINARI, Cochrane Library and Google Scholar. Relevant grey literature was obtained through online searches. The funnel plot and Egger's regression test were used to see publication bias, and the I-squared was applied to check the heterogeneity of the studies. Cross-sectional, case-control and cohort studies that were conducted in Ethiopia were also be included. The Joanna Briggs Institute checklist was used to assess the quality of the studies and was included in this systematic review. Data entry and statistical analysis were carried out using RevMan 5.4 software and Stata 14. Result After reviewing 1,125 studies, 26 studies fulfilling the inclusion criteria were included in the meta-analysis. The pooled prevalence of birth asphyxia in Ethiopia was 19.3%. In the Ethiopian context, the following risk factors were identified: Antepartum hemorrhage(OR: 4.7; 95% CI: 3.5, 6.1), premature rupture of membrane(OR: 4.0; 95% CI: 12.4, 6.6), primiparas(OR: 2.8; 95% CI: 1.9, 4.1), prolonged labor(OR: 4.2; 95% CI: 2.8, 6.6), maternal anaemia(OR: 5.1; 95% CI: 2.59, 9.94), low birth weight(OR = 5.6; 95%CI: 4.7,6.7), meconium stained amniotic fluid(OR: 5.6; 95% CI: 4.1, 7.5), abnormal presentation(OR = 5.7; 95% CI: 3.8, 8.3), preterm birth(OR = 4.1; 95% CI: 2.9, 5.8), residing in a rural area (OR: 2.7; 95% CI: 2.0, 3.5), caesarean delivery(OR = 4.4; 95% CI:3.1, 6.2), operative vaginal delivery(OR: 4.9; 95% CI: 3.5, 6.7), preeclampsia(OR = 3.9; 95% CI: 2.1, 7.4), tight nuchal cord OR: 3.43; 95% CI: 2.1, 5.6), chronic hypertension(OR = 2.5; 95% CI: 1.7, 3.8), and unable to write and read (OR = 4.2;95%CI: 1.7, 10.6). Conclusion According to the findings of this study, birth asphyxia is an unresolved public health problem in the Ethiopia. Therefore, the concerned body needs to pay attention to the above risk factors in order to decrease the country's birth asphyxia. Review registration PROSPERO International prospective register of systematic reviews (CRD42020165283).